Analisa Pencarian Jalur Terbaik Pada Transportasi Laut Pengiriman Batubara Dengan Menerapkan Ant Colony Optimization Berbasis Website - Astrid Diandra Maulidina; Zulfa Fitri Ikatrinasari (Universitas Mercu Buana, 2022)
The high level of national coal production is certainly directly proportional to the demand for coal shipments through sea transportation. Minimizing delays in coal shipments is the main focus that must be resolved to meet the satisfaction of customers, especially for coal shipments from North Kalimantan which reached 29% delay time. The purpose of this research is to be able to find out the value of optimization in choosing the best path in shipping coal through sea transportation and create website-based application designs. This study uses quantitative research methods where calculations using ant colony optimization algorithms (ACO) based on secondary data with website-based MATLAB GUI tools. That way, this research is expected to provide recommendations for marine transportation, especially the shipping industry based on the goals to be achieved in this study.